O vocabulário alencariano de O Sertanejo: uma análise léxico-semântica - Queiroz, Silvana Rodrigues de Souza (2006)
This paper performs a lexical-semantic study of the main nouns in the flora and fauna lexical fields of the novel O Sertanejo by José de Alencar. With the purpose of verify lexical aspects used by the author in the establishment of the geographical space named by him as sertão. It is still tried to demonstrate that the formation of these lexical fields are revealing of the author s intention in relation to his major proposal: to create a literature that shows the Brazilian ways in language, culture, nature or geography. The theoretical model chosen to organize and analyse the lexical fields was the Concept System by Rudolf Hallig and Walter von Wartburg, which was published in 1952 with the purpose of offering support and orientation to lexical books. This system proposes the concept division of the world into three major categories: A Universe; B Man; C Relationships between man and universe. With the contextual descriptions and flora and fauna field analysis performed, we consider our hypothesis confirmed since it was possible to verify, via lexicon, that the sertão of José de Alencar is not the sertão of Ceará, Brazil, as the previous assumption, since he was born in Ceará; but the sertão of José de Alencar is a literary one, it is the national sertão, it is Brazil itself. Through the idealization of the sertão, the description of the nature, José de Alencar creates and reveals the Brazilian nation, seeking its literary, linguistic, and cultural autonomy. Therefore, portraying the flora and fauna, in all its diversity and beauty, was one of the ways to build our nationality. The language and the literature become, to José de Alencar, the fundamental tool in the constitution of an identity to a recently independent nation. This way, we can notice that the representative lexical items of the conceptual fields of flora and fauna in José de Alencar s novel O Sertanejo were revealing of his intentions to make our literature, our language, our culture into genuine Brazilian manifestations.